Experimental and theoretical coupled approaches for the analysis of radiative transfer in photoreactors containing particulate media: Case study of TiO2 powders for photocatalytic reactions. (2nd November 2021) - Ribeiro, E.; Plantard, G.; Cornet, J.-F.; Gros, F.; Caliot, C.; Goetz, V.
Highlights: A particulate media radiative properties prediction approach is presented. Radiative transfer equation was solved by Monte Carlo and Two Flux methods. The solution of radiant energy transfer in a parallel-plane reactor was achieved. Corrections were added to the Two Flux approach for transmittance predictions. Local radiant energy modeling was achieved for a case study TiO2 material. Abstract: The analysis of radiative transfer in photoreactors is often crucial for operating efficient photoreactions. This article aims to present a complete experimental and theoretical coupled approach allowing radiative transfer analysis of photoreactors containing particulate media. TiO2 powder, widely used in photocatalysis, was selected as a case study material for this work. First, Mie theory was used and adapted to assess the effective properties of heterogenous powders. A home-made experimental bench allowing normal-hemispheric transmittance measurement was settled. Theoretical and experimental evaluations of the radiative properties were compared and appear to match each other. The second part of the work consisted in both transmittance and local radiant energy modeling through Monte Carlo and Two Flux models using the previously defined radiative properties as entry parameters. The comparison of experimental and modeled transmittance highlighted the consistence of these models which were then used to describe the radiant energy evolution inside a parallel-plane photoreactor.